2022
DOI: 10.1007/s40122-022-00358-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of M-Health-Based Core Stability Exercise Combined with Self-Compassion Training for Patients with Nonspecific Chronic Low Back Pain: A Randomized Controlled Pilot Study

Abstract: Introduction: Nonspecific chronic low back pain (NCLBP) is a leading contributor to disease burden worldwide, and the management of NCLBP has always been a problem. This study is designed to explore the feasibility and efficacy of m-health-based core stability exercise (CSE) combined with self-compassion training (SCT) and compare it with m-health-based CSE alone for the management of NCLBP. Methods: This study is a pilot, patient-blinded randomized controlled trial. Participants with NCLBP were randomized int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…These positive effects were demonstrated by Zheng et al 26 once on pain (NRS) and function (Roland and Morris Disability Questionnaire; RMDQ) using m‐Health‐based core stability exercises after 4 and 16 weeks, with patients who additionally performed self‐compassion training achieving these effects earlier. Two other studies of a mobile app delivering multidisciplinary treatment for pain‐related LBP found the app had a positive effect and a stronger pain reduction on VAS pain compared to the control group after 12 weeks.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These positive effects were demonstrated by Zheng et al 26 once on pain (NRS) and function (Roland and Morris Disability Questionnaire; RMDQ) using m‐Health‐based core stability exercises after 4 and 16 weeks, with patients who additionally performed self‐compassion training achieving these effects earlier. Two other studies of a mobile app delivering multidisciplinary treatment for pain‐related LBP found the app had a positive effect and a stronger pain reduction on VAS pain compared to the control group after 12 weeks.…”
Section: Discussionmentioning
confidence: 88%
“…16 Nevertheless, positive effects are attributed to digital exercise treatments, either with educational component 15,17 or without. 25 These positive effects were demonstrated by Zheng et al 26 for pain-related LBP found the app had a positive effect and a stronger pain reduction on VAS pain compared to the control group after 12 weeks. 12,13 In contrast to this study, in which the app group differed significantly from the control group in terms of ODI at 4 and 8 weeks, subjects in the app group were only superior to those in the control group in the study by Priebe et al 13 in functional outcomes.…”
Section: Pain Impairment In Daily Lifementioning
confidence: 82%
“…Sample size calculation will be based on the results of our pilot study [34]. We found a mean difference of 5.5 for RMDQ with a standard deviation of 4.7 in the intervention group and a mean difference of 3.1 with a standard deviation of 4.8 in the control group at 16week follow-up.…”
Section: Sample Size {14}mentioning
confidence: 92%
“…We recruited participants from April 2021 to January 2022 via advertisement posted at the rehabilitation department of the First Afliated Hospital of Sun Yat-Sen University. Te NCLBP group was enrolled based on the following criteria: the participants should meet the medical diagnostic standards for NCLBP [4], aged 18∼59 years with low back pain between the twelfth rib and the gluteus sulcus, pain intensity between 2∼5/10 according to the numerical rating scale (NRS) [13,15,25], and symptoms lasting for at least 3 months. For the healthy control (HC) group, participants were matched with the NCLBP group for demographic data such as sex, educational status, height, weight, age, and so on and with no symptom of low back pain.…”
Section: Participantsmentioning
confidence: 99%
“…Finally, we excluded participants who had conditions that made them unable to cooperate with the examination (cognitive disorder, psychosis, current self-harm or suicidal ideation, major depression or anxiety, etc.) [25].…”
Section: Participantsmentioning
confidence: 99%